Definição de estratégias de lances de concessionárias de distribuição em leilões de energia elétrica do tipo loose pool baseadas em teoria de jogos - Alvarenga, Vinícius Blaya (Universidade Federal de São Carlos, 2021)
Due to the deregulation of the Brazilian Electricity Sector and the definition of the New Model of the Electricity Sector in Brazil in 2004, generation, commercialization and distribution companies have become able to bid supply and demand in electric energy auctions authorized by the National Agency of Electric Energy (ANEEL) and carried out by the Electric Energy Trading Chamber (CCEE) to encourage competitiveness among different companies in each activity. Thus, this paper aims at defining bidding strategies for the purchase of electricity by distribution companies using Game Theory, avoiding their exposure to (generally high) difference settlement prices by the Independent Market Operator (OIM). To accomplish this, it has been implemented an auction model to simulate the supply and demand allocation by the OIM for a 6-bus test-system considering active power balance on system buses and minimum and maximum active power flow limits in transmission lines. As a direct result of the proposed methodology, it is possible to define the best purchase bidding strategies in an auction in terms of the number of competitors and the number of accounted bids.
Definition of bidding strategies for distribution companies in loose pool electricity auctions based on game theory
Keywords: Estratégias de lances; Leilões de energia elétrica; Mercados de energia elétrica; Teoria de jogos; ENGENHARIAS::ENGENHARIA ELETRICA::SISTEMAS ELETRICOS DE POTENCIA::TRANSMISSAO DA ENERGIA ELETRICA, DISTRIBUICAO DA ENERGIA ELETRICA